Transtorno do Espectro Autista: Direitos Fundamentais - Olinda, Antonia Gomes de (2023)
The book presents evidence on the fundamental rights of Autism Spectrum Disorder, a neurological condition that affects the development of the brain, mainly affecting social communication, social interaction and behavior. It is a condition that manifests itself in different ways in different people, and is considered a spectrum because it encompasses a wide range of symptoms and levels of severity. Although there is no cure for ASD, interventions and therapies can help improve the quality of life of people with autism. Some common treatments include behavioral therapy, occupational therapy, speech therapy and specialized education. The support and understanding of family, friends, parents and the community also play a crucial role in supporting people with ASD. It is important to emphasize that each person with ASD is unique, and their needs and abilities vary. The main goal is to provide the necessary support to help people with ASD develop their full potential and live a full and inclusive life.